2013
DOI: 10.1051/0004-6361/201220915
|View full text |Cite
|
Sign up to set email alerts
|

Hα3: an Hαimaging survey of HI selected galaxies from ALFALFA

Abstract: Context. We present the analysis of the galaxy structural parameters from Hα3, an Hα narrow-band imaging follow-up survey of ∼800 galaxies selected from the HI Arecibo Legacy Fast ALFA Survey (ALFALFA) in the Local supercluster, including the Virgo cluster, and in the Coma supercluster. Aims. Taking advantage of Hα3, which provides the complete census of the recent star-forming, HI-rich galaxies in the local universe, we aim to investigate the structural parameters of the young (<10 Myr) and the old (>1 Gyr) s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 109 publications
(151 reference statements)
10
59
0
Order By: Relevance
“…A KolmogorovSmirnov test indicates that the probability that the two samples are drawn from the same parent population is 2 × 10 −9 %, i.e., they differ significantly. This is consistent with an Hα disk truncated by ram-pressure (Fumagalli & Gavazzi 2008), such as in the prototype NGC 4569 in Virgo or in NGC 4848 in Coma (Fossati et al 2012). These cases are different from the HI-rich systems, which tend to host Hα emission extended across the entire disk (as discussed in Paper IV).…”
Section: Activity On Nuclear Scalesupporting
confidence: 79%
See 1 more Smart Citation
“…A KolmogorovSmirnov test indicates that the probability that the two samples are drawn from the same parent population is 2 × 10 −9 %, i.e., they differ significantly. This is consistent with an Hα disk truncated by ram-pressure (Fumagalli & Gavazzi 2008), such as in the prototype NGC 4569 in Virgo or in NGC 4848 in Coma (Fossati et al 2012). These cases are different from the HI-rich systems, which tend to host Hα emission extended across the entire disk (as discussed in Paper IV).…”
Section: Activity On Nuclear Scalesupporting
confidence: 79%
“…Paper II ) outlined the analysis, including the study of the scaling relations between HI mass, stellar mass, star formation, and the environmental conditions. Paper IV (Fossati et al 2013) will analyze the structural properties of galaxies in the Local and Coma superclusters, and Paper V will contain the Hα3 data (fluxes and images) in the Coma supercluster.…”
Section: Introductionmentioning
confidence: 99%
“…15 An accurate study of the star-formation properties of low-luminosity cluster galaxies has been made possible owing to the narrow-band Hα imaging data that our team has obtained in these past years. By comparing the Hα morphology of galaxies in Virgo, Coma and A1367 to those of field galaxies selected according to similar criteria, Fossati et al (2013) have shown that the star-forming disk of LTGs, including dwarf systems, is truncated once the galaxies are devoid of their gas (Fig. 11).…”
Section: Star Formationmentioning
confidence: 99%
“…The angular resolution of the HI, CO, and farinfrared images now available thanks to interferometric observations in the radio domain and to the superior quality of the instruments on board of Herschel revealed that cluster galaxies have truncated gaseous and dust discs (Fumagalli et al 2009;Boselli et al 2014b;Cortese et al 2012a;Davis et al 2013), suggesting that the mechanism responsible for their stripping acts outsidein. The star formation activity of the late-type galaxies in clusters is also systematically reduced with respect to that of field objects (Kennicutt 1983;Gavazzi et al 1998Gavazzi et al , 2002aGavazzi et al , 2006b and is limited to the inner disc (Koopmann & Kenney 2004;Boselli & Gavazzi 2006;Cortese et al 2012b;Fossati et al 2013). The correlation between the molecular gas content and the activity of star formation (e.g.…”
Section: Introductionmentioning
confidence: 99%